Soil erosion and sediment yield assessment using RUSLE and GIS based approach in a forest watershed in Kandi region of Punjab - YOUSUF, ABRAR; SINGH, M.J.; BENIPAL, AMANPREET KAUR; SHARMA, NAVNEET (Journal of Soil and Water Conservation, 2023)
The Revised Universal Soil Loss Equation (RUSLE) integrated with the sediment delivery ratio (SDR) model employed in the GIS environment has been used to quantify the soil erosion and sediment yield for a small reservoir (Takarla dam) located in the Kandi region of Punjab, India. The catchment area of Takarla dam is 72.6 ha. The various layers including rainfall erosivity factor, soil erodibility factor, Slope length and steepness factor and crop management factor were prepared in ArcGIS to estimate the average annual soil loss. The SDR for the dam watershed was obtained by employing different empirical equations. The sedimentation rate and sediments collected in the dam was assessed for the last 20 years. The results of the present study revealed that the average annual soil loss varied from 0 to 12.8 t ha-1 year-1 for Takarla dam. The sediments deposited in the dam over 20 years estimated to be 142603.8 tonnes. The results of the present study may provide an insight for policy makers to design and execute the watershed management practices to reduce erosion hazard and sediment accumulation in the reservoirs.